Happenstance found / 1. - Catanese, P. W. (Catanese, P. W. Books of Umber, 2009)
Twelve-year-old Happenstance wakes up in a cave with no idea how he got there, or who he is, but merchant and royal advisor Lord Umber helps Hap and his two friends escape from the caverns.